Live Assistance And Tracking System(LATS) using Cloud and IoT - Katkhede, P.V; Todmal, V; Pandey, D; Saini, A; Patil, BA (International Journal of Computer Sciences and Engineering, 2019)
Current socio-economic situations around the world have seen a drastic rise in crime rate all over the world, which proves difficult to control for any type of authorities and most of the resources are wasted on crimes which have been already committed. The emphasis of our system is to stop the crime before it is even anticipated ensuring safety of a loved individual and also saving the extra resources the authorities may encounter. Our system proposes an immediate live assistance in case of an emergency by special armed task force designed to encounter dangerous situations and kill the crime in the cradle.